1946
DOI: 10.1172/jci101678
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Shock. Xii. Hemodynamic Effects of Alterations of Blood Viscosity in Normal Dogs and in Dogs in Shock 1

Abstract: Striking differences have been noted between dogs in hemorrhagic and in tourniquet shock (1). In both types, there is a reduction in blood volume, but the hematocrit and blood viscosity, which remain substantially unchanged in hemorrhagic shock, increase in tourniquet shock. At a blood pressure level of 80 to 100 mm. Hg, the dog in hemorrhagic shock is only mildly depressed and is still responsive to ordinary stimuli; whereas, in tourniquet shock he is already severely depressed, unresponsive to strong stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1947
1947
1975
1975

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Absolute viscosity of a fluid can be determined by passing the fluid through a tube of known length and radius while measuring the rate of flow and the difference in pressure between the ends of the tube. This relationship is expressed by the following formula: fTr q81' (1) where vi = absolute viscosity in grams sec. per cm.3; q = volumetric rate of flow as cm.'…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Absolute viscosity of a fluid can be determined by passing the fluid through a tube of known length and radius while measuring the rate of flow and the difference in pressure between the ends of the tube. This relationship is expressed by the following formula: fTr q81' (1) where vi = absolute viscosity in grams sec. per cm.3; q = volumetric rate of flow as cm.'…”
Section: Methodsmentioning
confidence: 99%
“…diameter, blood behaves as a homogeneous mixture (10), and at physiological pressures its flow is laminar (8). According to formula (1), viscosity is independent of the character of the vessel wall and a tube may be substituted for a blood vessel to allow an accurate determination of length and radius. The insertion of such a branching system does not invalidate Poiseuille's law.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hg in mean arterial pressure. It has been pointed out (38) that the blood pressure may be a misleading guide to the state of the animal when the blood viscosity is abnormally high due to a high hematocrit. In such event, the blood flow, as indicated by cardiac output, is very poor in spite of nearly normal blood pressure.…”
Section: Series Imentioning
confidence: 99%
“…In a hemodynamic evaluation of shock, Seligman 1 indicated that enhanced blood viscosity promoted the onset of irreversibility, presumably through an effect on flow. More recently Richardson 2 assigned a major role to viscosity in the development of a diminished cardiac output during acute normovolemic polycythemia.…”
mentioning
confidence: 99%